Developing Organizational Behavior by Motivating Employees - Ciprian GRIGORESCU; Angelica Musat; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2022)
the present research propose to analyze psychological mechanisms of job and how to make employees to fell motivated to develop organizational behavior. There are internal and external factors increasing motivation. Income instated to be one of the motivations instruments while the significance of it varies by person and institution.
Keywords: motivation; management; organizational behaviors